The use of seismic tomography to describe the upper crustal structure beneath the Chalupas Caldera, Ecuador - Paredes, Cristopher Daniel (2021)
The Chalupas Caldera is a rhyolitic volcano located in the Eastern Cordillera to the Southeast of the Cotopaxi Volcano in the Ecuadorian Andes. It is supposedly fed by a huge magmatic chamber below the caldera. For studying the Chalupas magmatic chamber, the tomographic models obtained by a Tarantola-Valette inversion and studied previously in the entire Ecuadorian region were used. The theoretical basis of the tomography method based on a Bayesian solution of the inverse problem is introduced. The process of the inverse problem regularization is obtained by an L-curve scheme to achieve an optimal solution. The seismic tomography images zoomed in the Chalupas region are well correlated with the main geological terranes and faults documented for the basement of Eastern Cordillera. Based on the tomographic images obtained, it can be assumed that there is not a magmatic chamber of considerable magnitude placed close to the surface underneath the Chalupas Caldera, since it does not present seismic and tomographic evidence to be able to assume a possible volcanic eruption before long. Furthermore, the images allow identifying that the seismic and thermal activity is located beneath the Cotopaxi Volcano as a vertical anomaly beneath the Northeast of Cotopaxi Volcano that corresponds to the phreatomagmatic activity observed in 2015.